MyDispense: Lessons from Global Collaboration in Developing a Pharmacy Educational Simulation Tool - Marian T Costelloe (University of Minnesota Libraries Publishing, 2017)
The current focus on global workforce development in pharmacy provides a perfect stage for continued and extended collaboration between educators, researchers, and practitioners. One such global educational project is the MyDispense Project, which is a collaborative journey that started with an educational need. MyDispense is an online pharmacy simulation tool that teaches dispensing skills to students. Development of the tool began as a need for Australian pharmacy students, but has been customized for other parts of the world as well. Since the project's launch in 2010, the ongoing use and development of the tool is a compelling story of success for global collaboration in pharmacy education. Lessons can be learned from this collaborative endeavour.   Type: Commentary